Critical Leaf Magnesium Thresholds and the Impact of Magnesium on Plant Growth and Photo-Oxidative Defense: A Systematic Review and Meta-Analysis From 70 Years of Research - Hauer-Jákli, Melanie; Tränkner, Merle (Frontiers in Plant Science, 2019)
Magnesium (Mg) deficiency in plants is a widespread problem affecting productivity and quality in agricultural systems and forestry. Although numerous studies addressed the effect of Mg deficiency on biomass and photosynthetic CO2 assimilation, a summary evaluation of the effect of Mg supply on plant growth and photosynthesis is so far missing. We performed a systematic review and meta-analysis to collect and combine all relevant scientifically published data on the relationship between Mg nutrition and parameters that can be related to plant growth such as root and shoot biomass, harvestable yield, net CO2 assimilation and antioxidant enzyme activities. Moreover, this data pool was used to calculate critical Mg leaf concentrations for biomass and net CO2 assimilation for various plant species. Summarizing all studies included in our analysis, adequate Mg supply enhances net CO2 assimilation by 140%, leading to a biomass increase of 61% compared to Mg deficient control plants. Biomass partitioning between shoot and root is not only sensitive to Mg nutrition, but highly affected by the experimental cultivation technique. If plants are grown under adequate Mg supply during initial growth stages before exposing them to Mg deficiency, the shoot-root ratio was not affected. Otherwise, the shoot-root ratio significantly decreased in contrast to Mg deficient control plants. Concentration of reactive oxygen species decreased under adequate Mg supply by 31% compared to Mg deficient plants, resulting in decreased activities of most antioxidant enzymes and metabolites under adequate Mg supply. We combined all published data relating leaf Mg concentrations to growth and found a critical leaf Mg range for dry weight between 0.1 and 0.2% which was valid for numerous crop species such as wheat, potato, rice, maize, sorghum and barley. Critical leaf Mg concentrations for net CO2 assimilation were higher than for biomass for most species, e.g., potato, rice, citrus, and cotton. In conclusion, our evaluation can be used to identify Mg nutritional status in plants and may help to optimize fertilization strategies. It quantifies the demand of Mg for various crop and tree species for maintaining important physiological processes such as net CO2 assimilation that is required for optimal plant growth and yield.